Convective flow, heat and mass transfer of Ostwald-de Waele fluid over a vertical stretching sheet - K. Vajravelu; K.V. Prasad; P.S. Datti; B.T. Raju (Journal of King Saud University: Engineering Sciences, 2017)
In this paper we study the combined buoyancy (due to thermal and species diffusion) effects on the flow, heat and mass transfer of a viscous, incompressible, Ostwald-de Waele fluid over a vertical stretching surface in the presence of a chemical reaction. The effects of variable thermal conductivity and the variable mass diffusivity are also considered. A similarity transformation is used to convert the partial differential equations into coupled nonlinear ordinary differential equations. Numerical solutions are obtained by the Keller-box method. The influences of sundry parameters on the velocity, temperature and the concentration fields are presented in figures and discussed in detail. The values of the skin friction coefficient, Nusselt number and the surface mass transfer for various values of the governing parameters are presented in tables. One of the interesting observations is that the influence of the buoyancy parameters increases the velocity. However, quite the opposite is true with the temperature and the mass concentration, for all values of the power law index and the reaction rate parameter. The results obtained reveal many interesting behaviors that warrant a further study of the non-Newtonian fluid phenomena, especially shear thinning phenomena. Shear thinning reduces the wall shear stress.